2013
DOI: 10.1111/bjd.12384
|View full text |Cite
|
Sign up to set email alerts
|

Sunbed use among subjects at high risk of melanoma: an Italian survey after the ban

Abstract: More skin cancer monitoring is needed at tanning centres, and educational campaigns should be promoted, especially for young women and subjects at high risk of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 23 publications
5
38
3
Order By: Relevance
“…As far as we are concerned, there are no studies specifically aimed to ascertain the prevalence and distribution of different phototypes and phenotypes within the Italian population; some indications can be drawn by data retrieved during screening prevention events, even if in some way they are controversial. For instance, in the population screened during the Italian Euromelanoma day 2010, 6.1% had phototype I, 18.6% II whilst a higher prevalence of dark phototypes (44.9% III and 30.4% phototype IV) was reported with respect to our population; moreover, a sunburn was reported to have taken place before 18 years of age in 35.2% [12]. In the previous similar events from 2005 to 2007, different figures were reported, more similar to those found in our study, with only 7.9% phototype IV and 39.9% phototype II [13].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…As far as we are concerned, there are no studies specifically aimed to ascertain the prevalence and distribution of different phototypes and phenotypes within the Italian population; some indications can be drawn by data retrieved during screening prevention events, even if in some way they are controversial. For instance, in the population screened during the Italian Euromelanoma day 2010, 6.1% had phototype I, 18.6% II whilst a higher prevalence of dark phototypes (44.9% III and 30.4% phototype IV) was reported with respect to our population; moreover, a sunburn was reported to have taken place before 18 years of age in 35.2% [12]. In the previous similar events from 2005 to 2007, different figures were reported, more similar to those found in our study, with only 7.9% phototype IV and 39.9% phototype II [13].…”
Section: Discussionmentioning
confidence: 48%
“…Carli et al [11] found that high counts of common naevi correlate with prevalence of atypical naevi independently of phototype, phenotype or sunburns. Stanganelli et al [12] conducted a survey of 4,703 people in the region Emilia-Romagna (northern Italy), showing that the use of sunbeds was higher in people already at a higher risk for melanoma, i.e. those with freckles, fair skin and eyes.…”
Section: Discussionmentioning
confidence: 99%
“…The study has been described extensively in Stanganelli et al [16]. Briefly, this project, called the "Save the skin", was developed by the Melanoma survey Unit of Istituto Oncologico Romagnolo (IOR), ForlĂŹ, associated with the Skin Cancer Unit of Istituto Scientifico Romagnolo per lo Studio e la Cura dei Tumori, Meldola (FC), in partnership with Centro di Studi Avanzati sull'Umanizzazione delle Cure e sulla Salute Sociale (Ce.Um.S.…”
Section: Methodsmentioning
confidence: 99%
“…Comprehensive meta-analysis reveals that the strongest evidence for a link between artificial UV and melanoma is among individuals first exposed to indoor tanning before the age of 35 [15] We designed this study to assess the behaviour of a population with high melanoma incidence which spends a lot of time seeking a suntan at easily accessible beaches. In a previous study, we investigated sunbed use [16], in this analysis we assess sun exposure attitudes, sunscreen and sunglass use during sun exposure and sunbed use, in particular among the young. We also estimated the number of melanoma cases in Italy attributable to sunbed use in youth and to excessive sun exposure.…”
mentioning
confidence: 99%
“…FernĂĄndez-Morano et al [1] report on behaviour, attitudes and awareness concerning sun exposure in adolescents aged 11-17 years living in southern Spain. Gandini et al [2] describe a previously published [3] young population consisting of beach visitors (88% of the cohort) and university students in Italy. Half of this population was younger than 35-years-old.…”
mentioning
confidence: 99%